2002
DOI: 10.1097/00008390-200204000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HER-2 in thick melanoma

Abstract: In this study we evaluated the overexpression status of HER-2 and its prognostic significance on survival in patients with thick cutaneous malignant melanoma. The immuno-alkaline phosphatase antigen detection technique was applied to archival diagnostic material from 51 patients with primary lesions measuring >or= 10 mm in Breslow thickness. Eleven additional patients with primary lesions measuring Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
2
10
0
1
Order By: Relevance
“…74 However, conflicting results have been published regarding the expression pattern of erbB-2 in primary and metastatic melanoma. [75][76][77][78] Our proteomic data supported the down-regulation of this receptor in WM-266-4 cells. Other molecules, such as melanoma-associated antigen p97, scavenger receptor and several solute carrier family proteins, also displayed different expression between these two cell lines.…”
Section: Characterization Of the Differential Expression Of Cell Surfsupporting
confidence: 57%
“…74 However, conflicting results have been published regarding the expression pattern of erbB-2 in primary and metastatic melanoma. [75][76][77][78] Our proteomic data supported the down-regulation of this receptor in WM-266-4 cells. Other molecules, such as melanoma-associated antigen p97, scavenger receptor and several solute carrier family proteins, also displayed different expression between these two cell lines.…”
Section: Characterization Of the Differential Expression Of Cell Surfsupporting
confidence: 57%
“…Although the relevance of HER2 in melanoma remains controversial,3, 22 expression of HER2 in melanoma tumor tissue and cell lines has been demonstrated 3, 36, 37. Regardless of its biological and/or clinical significance, the EST049 melanoma cell line can be regarded as a model to study the negative effect of HER2 on MHC class I antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 is a 185‐kDa glycoprotein member of the epidermal growth factor receptor family of tyrosine kinases and considered one of the most attractive targets for immunotherapeutic interventions 1. This oncogene is selectively over‐expressed in a broad variety of human tumors including 25–40% of breast, ovarian, gastric, renal, esophageal and colorectal carcinomas and a small proportion of human melanomas2–6 and as a cell surface molecule it is accessible both to antibody‐ and T cell‐based approaches. Moreover, HER2 can be regarded as an indispensable tumor antigen, since tumors over‐expressing HER2 are dependent on this oncogene for their survival and silencing consequently leads to growth arrest and/or apoptosis induction 7…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional data were available on 298 proteins. Thirty-one selected proteins, including γ-catenin/plakoglobulin (Silye et al , 1998; Sanders et al , 1999; Zhang and Hersey, 1999; Krengel et al , 2004; Kreizenbeck et al , 2008), Her2/neu (Persons et al , 2000; Fink-Puches et al , 2001; Eliopoulos et al , 2002; Potti et al , 2003a, 2004; Kluger et al , 2004), estrogen receptor-α (Cohen et al , 1990; Schmidt et al , 2006), matrix metalloproteinase-26, and matrix metalloproteinase-28 (Kuivanen et al , 2005), were found not to be expressed in melanoma cells and 18 proteins such as endothelin-3 (Tang et al , 2008), focal adhesion kinase (Hess et al , 2005), matrix metalloproteinase-1 (Nikkola et al , 2001, 2002), and telomerase (Batinac et al , 2007; Zygouris et al , 2007) were evaluated by IHC but cross-sectional data were not reported in their corresponding manuscripts. Among the included proteins, 274 were evaluated in progression studies but a much smaller subset, 148, had their expression levels correlated with Breslow thickness.…”
Section: Summary Of Eligible Cross-sectional Data From the Available mentioning
confidence: 99%